DIY assessment feedback: Building engagement, trust and transparency in the feedback process - Smith, Matthew; Lowe, Cassie (Journal of University Teaching and Learning Practice, 2021)
This study evaluates a novel assessment and feedback process in which students were tasked with actively engaging in the feedback process in a ‘DIY’ – do-it-yourself – assessment feedback workshop. The research team set out to explore how an active participation in the construction of the assessment criteria and utilisation of that co-constructed criteria would affect the students’ engagement with assessing their own work. Through providing the space in which students were encouraged to use criteria to mark their own work, the research team aimed to build the students’ trust and confidence in the transparency of the assessment process. The main findings of this study have shown the value of this DIY assessment feedback workshop, as it has proven to encourage a deeper level of reflection in the student participants and catalysed a greater connection between the learning process of assessment feedback with both their past and future assessments.